Investigating the correlation between tertiary lymphoid structures and clinical outcomes in pancreatic ductal adenocarcinoma: insights into tumor immunology - Hu, Lingbo; Xiao, Yanhong; Jiang, Ning; Hu, Yufen; Qiu, Liewang; Geng, Bo (Frontiers in Oncology, 2025)
Pancreatic ductal adenocarcinoma (PDAC) is associated with poor prognosis and high mortality rates, necessitating the identification of reliable biomarkers for patient stratification. This study investigates the prognostic significance and biological functions of tertiary lymphoid structures (TLS) in PDAC. We analyzed clinical data from 65 PDAC patients and RNA sequencing data from The Cancer Genome Atlas (TCGA) to evaluate the presence of TLS and its impact on overall survival (OS) and recurrence-free survival (RFS). Our results demonstrate that patients with intratumoral TLS (iTLS+) exhibit significantly improved OS and RFS compared to those without iTLS (iTLS-). Additionally, the presence of TLS correlates with enhanced immune cell infiltration, including increased levels of B cells, T cells, and plasma cells, suggesting a more active anti-tumor immune response in the TLS+ group. Furthermore, we found significant differences in gene expression between TLS+ and TLS- groups, particularly in pathways related to tumor proliferation and immune regulation. Notably, our findings indicate that the mutation frequency of key oncogenes, such as TP53, differs significantly between these groups, potentially influencing patient outcomes. This study underscores the potential of TLS as a prognostic biomarker in PDAC and highlights their role in modulating the tumor microenvironment. Our findings pave the way for further research into TLS-targeted therapeutic strategies aimed at improving the clinical management of pancreatic cancer.